Efficacy of alprostadil for preventing of contrast-induced nephropathy: A meta-analysis - Jing-Zhan Zhang (Nature Portfolio, 2017)
Abstract Contrast-induced nephropathy (CIN) has become the third-leading cause of hospital-acquired acute renal injury. Although alprostadil has been proposed as an effective preventative measure, this conclusion remains inconsistent. Thus, we performed a meta-analysis of the published studies on this topic to evaluate the preventative effect of alprostadil on CIN. Databases, including PubMed, the Web of Science, Cochrane Library, Wanfang, the China Biological Medicine Database (SinoMed) and the China National Knowledge Infrastructure (CNKI) were systematically searched. Nineteen clinical trials involving 2267 individuals were identified. We utilized a random or a fixed effect model to calculate the pooled odd ratios (ORs) and the standardized mean differences (SMD), respectively. Compared to the control group, the CIN risk decreased significantly in the alprostadil group (P < 0.00001, OR = 0.29, 95% CI = 0.21–0.39). In the subgroup of coronary angiography patients, the use of alprostadil also decreased the risk of CIN (P < 0.00001, OR = 0.27, 95% CI: 0.19–0.39). In conclusion, Alprostadil might be associated with a significant reduction in postcontrast Scr, BUN and CysC level and decrease the incidence of CIN.